Predictors and long-term outcome of intracranial hemorrhage after thrombolytic therapy for acute ischemic stroke—A prospective single-center study - Fekete, Klára Edit; Héja, Máté; Márton, Sándor; Tóth, Judit; Harman, Aletta; Horváth, László; Fekete, István (Frontiers in Neurology, 2023)
Introduction Acute ischemic stroke (AIS) is a potentially devastating disease with high disability and mortality. Recombinant tissue plasminogen activator (rt-PA) is an effective treatment with a 2–8% possible risk for symptomatic intracranial hemorrhage (sICH). Our aim was to investigate the risk factors and long-term clinical outcomes of ICH in patients after rt-PA treatment. Methods Consecutive patients with AIS, thrombolysed at the Department of Neurology, University of Debrecen, between 1 January 2004 and 31 August 2016 were enrolled prospectively. Risk factors, stroke severity based on the National Institute of Health Stroke Scale (NIHSS), functional outcome using the modified Rankin scale, and mortality at 1 year were compared in patients with and without ICH following rt-PA treatment. We evaluated clinical characteristics and prognosis by hemorrhage type based on the Heidelberg Bleeding Classification. Descriptive statistics, the chi-square test, the Mann–Whitney U-test, ANOVA, the Kruskal–Wallis test, a survival analysis, and logistic regression were performed as appropriate. Results Out of 1,252 patients with thrombolysis, ICH developed in 138 patients, with 37 (2.95%) being symptomatic. Mean ages in the ICH and non-ICH groups differed significantly (p = 0.041). On admission, the 24-h NIHSS after thrombolysis was higher in patients with ICH (p < 0.0001). Large vessel occlusion was more prevalent in patients with ICH (p = 0.0095). The ICH risk was lower after intravenous thrombolysis than intra-arterial or combined thrombolysis (p < 0.0001). Both at 3 months and 1 year, the outcome was worse in patients with ICH compared to patients without ICH group (p < 0.0001). Mortality and poor outcome were more prevalent in all hemorrhage types with a tendency for massive bleeding associated with unfavorable prognosis. At 3 months with the logistic regression model, the worse outcome was detected in patients with ICH after thrombolysis, at 1 year in patients with ICH after thrombolysis and smoking. Discussion Older age, higher NIHSS, large vessel occlusion, and intra-arterial thrombolysis may correlate with ICH. The unfavorable outcome is more common in patients with ICH. Precise scoring of post-thrombolysis bleeding might be a useful tool in the evaluation of the patient's prognosis. Our findings may help to identify predictors and estimate the prognosis of ICH in patients with AIS treated with rt-PA.